Diffusion of IT in Singapore schools : a process framework. - Tang, Pui See. (2010)
In response to the dominant "techno-determinist" and effects-oriented perspectives in the research of IT in education, the study adopted a process framework to examine how IT interacted in real settings with real people. The process framework is meant to revise the classical diffusion approach that focused primarily on the outcome of adoption. Composed by the "context" and "actors" dimensions, the process framework focused on what is being done with IT (implementation) than what IT has done (consequences). Essentially, the study looked into two kinds of communication processes, communication with sender and "communication" with technology — how the innovation was communicated and how schools and teachers dealt with the innovation.